2022
DOI: 10.1177/23821205221079567
|View full text |Cite
|
Sign up to set email alerts
|

Using Individual Assessments as a Tool for Formative Feedback on Emotional Intelligence Training Programs in Healthcare Learners

Abstract: Introduction Emotional Intelligence (EI) is a skillset that influences and impacts an individual's ability to create, foster, and maintain strong relationships. In healthcare settings optimal patient centered care exists when teamwork, critical thinking, selfless service, integrity, and emotional intelligence are effectively practiced. While various methods exist to teach EI in the preprofessional and professional settings, the assessment of the efficacy of these types of training remains elusive. We propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, authors such as Brackett & Mayer [ 52 ], Matthews et al [ 53 ], and Mayer et al [ 28 ] found low correlations between the constructs of the MSCEIT model and the EQ-i model. Chandrapal et al [ 165 ] argue that there could be bias in self-report tests or a limitation in their assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, authors such as Brackett & Mayer [ 52 ], Matthews et al [ 53 ], and Mayer et al [ 28 ] found low correlations between the constructs of the MSCEIT model and the EQ-i model. Chandrapal et al [ 165 ] argue that there could be bias in self-report tests or a limitation in their assessments.…”
Section: Discussionmentioning
confidence: 99%
“… Empirical Qualitative Davies et al [ 179 ]; Mansel and Einion [ 180 ] Interview 2 Applied to Quantitative Num. Empirical Quantitative Ahmed et al [ 107 ]; Alotaibi et al [ 181 ]; Araujo and Taylor [ 156 ]; Aritzeta et al [ 112 ]; Arnatt and Beyerlein [ 166 ]; Ayoko et al [ 144 ]; Bartone et al [ 159 ]; Boyatzis et al [ 133 ]; Carmeli [ 15 ]; Chandrapal et al [ 165 ]; Chang et al [ 153 ]; Chaudhary et al [ 182 ]; Clarke [ 145 , 167 ]; Côté et al [ 115 ]; Cummings et al [ 140 ]; Doan et al [ 126 ]; Downey et al [ 183 ]; Du et al [ 184 ]; Dulewicz and Higgs [ 118 ]; Edelman and van Knippenberg [ 134 ]; Emery [ 137 ]; Espinosa et al [ 160 ]; Fareed et al [ 161 ]; Furukawa and Kashiwagi [ 185 ]; Gavin et al [ 146 ]; Harrison et al [ 108 ]; Higgs and Aitken [ 186 ]; Hong et al [ 139 ]; Hur et al [ 109 ]; Jena and Goyal [ 164 ]; Judge and Bono [ 119 ]; Judge et al [ 60 ]; Judge et al [ 61 ]; Jung and Yoon [ 149 ]; Kellet et al [ 143 ]; Stubbs Koman and Wolff [ …”
Section: Tablementioning
confidence: 99%
“…They can be as simple as low-cost online modules or as complex and costly as executive coaching. Moreover, the topics discussed in EI lectures may differ, with some emphasizing mindfulness, burnout, or resilience [49]. One study from Norway used storytelling as a method for teaching EI, which appeared to benefit students' reflections on their role in the workplace.…”
Section: Discussionmentioning
confidence: 99%